2020
DOI: 10.2147/cmar.s269774
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Noncoding RNA LINC00839 Promotes the Malignant Progression of Osteosarcoma by Competitively Binding to MicroRNA-454-3p and Consequently Increasing c-Met Expression</p>

Abstract: This study was conducted to determine the expression and prognostic relevance of long intergenic non-protein coding RNA 839 (LINC00839) in osteosarcoma (OS) and to explore the detailed roles of LINC00839 in regulating OS cell activities and the mechanisms responsible for its cancer-promoting activity in OS. Methods: The expression of LINC00839 in OS tissues and cell lines was determined by quantitative reverse transcription-polymerase chain reaction. After LINC00839 knockdown, cell counting kit-8 assay, flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…In addition, the role of lncRNAs in osteosarcoma is currently of significant interest to many researchers. Previous studies have demonstrated the relationship between lncRNAs and tumorigenesis [ 9 , 10 ], metastasis [ 11 ], progression [ 12 ], and chemotherapeutic drug resistance [ 13 ] in osteosarcoma. Unfortunately, there is limited intervention research on the impact of potential prognostic lncRNA signatures for osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the role of lncRNAs in osteosarcoma is currently of significant interest to many researchers. Previous studies have demonstrated the relationship between lncRNAs and tumorigenesis [ 9 , 10 ], metastasis [ 11 ], progression [ 12 ], and chemotherapeutic drug resistance [ 13 ] in osteosarcoma. Unfortunately, there is limited intervention research on the impact of potential prognostic lncRNA signatures for osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…LINC00839 acts as an oncogenic gene and is signi cantly upregulated in human cancers including breast cancer and osteosarcoma [11,12]. In our study, we noticed that LINC00839 level was widely higher in NPC tissues from GEO dataset and cell lines than the normal tissues and NP-69.…”
Section: Discussionmentioning
confidence: 54%
“…LINC00839 has been veri ed as a cancer-promoting factor in multiple malignancies, and its dysregulation is closely correlated with tumor initiation, development and progression. In osteosarcoma, LINC00839 facilities the malignant development of cancer cell through competitively binding to miRNA-454-3p and enhancing the expression of c-Met [11]. LINC00839 is upregulated in chemo-resistant breast carcinoma cells and tissues, and high level of LINC00839 is associated with a poor prognosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Long intergenic non-protein coding RNA 839 (LINC00839) was also studied in breast cancer [100] and osteosarcoma [101]. Its upregulation correlated with bad prognosis in both cases.…”
Section: Lncrna Associated With Nb Regressionmentioning
confidence: 99%